Thinking, Walking, Talking: Integratory Motor and Cognitive Brain Function - Leisman, Gerry; Moustafa, Ahmed A.; Shafir, Tal (Frontiers in Public Health, 2016)
In this article, we argue that motor and cognitive processes are functionally related and most likely share a similar evolutionary history. This is supported by clinical and neural data showing that some brain regions integrate both motor and cognitive functions. In addition, we also argue that cognitive processes coincide with complex motor output. Further, we also review data that support the converse notion that motor processes can contribute to cognitive function, as found by many rehabilitation and aerobic exercise training programs. Support is provided for motor and cognitive processes possessing dynamic bidirectional influences on each other.